The peak efficiency of initial antihypertensive therapy of primary open-angle glaucoma considering the factors that reduce adherence to the ther - N.G. Glazko; T.M. Volobueva; E.A. Egorov (РМЖ "Клиническая офтальмология")
N.G. Glazko, T.M. Volobueva, E.A. Egorov Pirogov Russian National Research Medical University, Moscow, Russian Federation Glaucoma treatment is a combined approach including selection of antihypertensive drugs to achieve the target pressure and their regular use by a patient as per the prescribed regimen. Along with a minimum number of instillations, prostaglandin analogues demonstrate the maximum hypotensive effect at the start of treatment. Patient adherence to therapy is a key aspect of successful therapy. However, continuous drug instillation leads to several side effects (such as dryness, hyperemia, burning sensation, itching, and blurred vision after the drug instillation) induced by exposure of preservatives (i. e., an ingredient of antihypertensive drops) to the eye surface. The lack of obvious improvement in the course of the disease, discomfortable use of the drops, side effects, and high cost of the drugs may lead to non-compliant instillation regimen, treatment refusal or unauthorized therapy change by a patient. Mitigation of the negative drug effect not only protects the eye surface, but also reduces negative emotions of patients resulted from continuous treatment burden. Successful glaucoma treatment and preservation of visual functions is possible in case of a harmonious combination of medical, psychological and financial factors that increase patients' satisfaction and, as a result, functional outcomes of the treatment. Keywords: initial glaucoma therapy, latanoprost, dorsolamide, glaucoma treatment-associated financial burden, undesirable effects of glaucoma therapy, adherence to glaucoma therapy. For citation: Glazko N.G., Volobueva T.M., Egorov E.A. The peak efficiency of initial antihypertensive therapy of primary open-angle glaucoma considering the factors that reduce adherence to the therapy. Russian Journal of Clinical Ophthalmology. 2024;24(4):200–205 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-6